Role of antibodies and IL17-mediated immunity in protection against pneumococcal otitis media. Issue 48 (21st November 2016) - Habets, Marrit N.; van Selm, Saskia; van Opzeeland, Fred J.; Simonetti, Elles; Hermans, Peter W.M.; de Jonge, Marien I.; Diavatopoulos, Dimitri A.
Highlights: Mucosal vaccination with PspA and CTB restricts pneumococcal colonization. Vaccination reduces influenza-virus induced pneumococcal otitis media. Protection was correlated with a balanced anti-PspA IgG1:IgG2a ratio. Vaccination induces a mucosal Th17 response against PspA. Mice deficient in IL-17 signaling were not protected by vaccination. Abstract: Widespread vaccination against Streptococcus pneumoniae (the pneumococcus) has significantly reduced pneumococcal disease caused by vaccine serotypes. Despite vaccination, overall pneumococcal colonization rates in children have not reduced and otitis media (OM) by non-vaccine serotypes remains one of the most common childhood infections. Pneumococcal surface protein A (PspA) has been shown to be a promising protein antigen to induce broad protection against pneumococcal colonization. However, its ability to protect against OM remains unclear. Using our previously established mouse model of influenza-virus induced pneumococcal OM, we here show that intranasal vaccination of mice with PspA together with the mucosal adjuvant CTB results in a decrease in pneumococcal load in the middle ears. This decrease correlated with the induction of PspA-specific IgA, a balanced IgG1:IgG2a antibody response and the induction of a mucosal Th17 response. Our data suggests that the IL-17 response to PspA is more important for protection against OM, whilst the presence of antibodies may be less important, as determined in mice deficient in IL-17 signaling or antibody production. Together, these results suggest that mucosal vaccination with PspA may not only protect against colonization, but also against the development of virus-induced pneumococcal OM.